1994
DOI: 10.1046/j.1468-2982.1994.1401037.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache in Acute Cerebrovascular Disease: A Prospective Clinical Study in 240 Patients

Abstract: To evaluate the clinical features of headache in stroke, a prospective study was carried out in 240 consecutive patients with acute stroke who had intact expressive function. Headache occurred in 38%: 32% of 195 patients with ischemic stroke and 64.5% of 45 patients with hemorrhagic stroke (p < 0.0001). Headache patients were younger (mean age 62 +/- 15 vs 67 +/- 11.5 years) than non-headache patients (p < 0.01). A history of previous vascular or tension-type headache was found in 40.5% of the headache group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
119
0
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(146 citation statements)
references
References 25 publications
16
119
0
11
Order By: Relevance
“…4,[8][9][10][11][12][13][14][15][16] In addition, we found that patients who developed headaches after tPA administration were younger, which is consistent with a previous observation. 17 One previous study reported a higher incidence of headache in cardioembolic infarcts than in TIAs, lacunar infarcts, or thrombotic infarcts.…”
Section: Discussionsupporting
confidence: 92%
“…4,[8][9][10][11][12][13][14][15][16] In addition, we found that patients who developed headaches after tPA administration were younger, which is consistent with a previous observation. 17 One previous study reported a higher incidence of headache in cardioembolic infarcts than in TIAs, lacunar infarcts, or thrombotic infarcts.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, severe headache was an early clinical marker signifi cantly associated with END in the logistic regression analysis (OR = 2.95). In a previous study by our group [28], the incidence of headache in cardioembolic stroke was 39% (severe-incapacitating 11% and mild-moderate intensity in 28%), which is similar to the frequency reported in other studies [29,30]. As far as we are aware, this is the fi rst study showing an association between severe headache at stroke onset and END in patients with cardioembolic infarction.…”
Section: Discussionsupporting
confidence: 86%
“…Headache is observed in about 15% to 40% of patients with acute ischemic stroke and is seen more often in patients with posterior circulation stroke (59%) [23] compared with other areas [24] . In this study, we found that headache can be an important sign of central vertigo.…”
Section: Mri (+) Mri (-)mentioning
confidence: 99%